2002
DOI: 10.1002/pola.10317
|View full text |Cite
|
Sign up to set email alerts
|

Cure kinetics of the ring‐opening metathesis polymerization of dicyclopentadiene

Abstract: Abstract:The cure kinetics of polydicyclopentadiene (pDCPD) prepared by ringopening metathesis polymerization with three different concentrations of Grubbs' catalyst was examined using differential scanning calorimetry (DSC). The experimental data were used to test several different phenomenological kinetic models. The data are best modeled with a "model-free" isoconversional method. This analysis reveals that the activation energy increases significantly for degree of cure greater than 60%. Catalyst concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
161
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 17 publications
8
161
0
Order By: Relevance
“…11 Furthermore, it has been observed that in addition to energy, bulk polymerization of DCPD occurs as a function of catalyst content, 11,12 yet the increased catalyst concentration of Experiment 14 did not yield any toughness recovery.…”
Section: Resultsmentioning
confidence: 99%
“…11 Furthermore, it has been observed that in addition to energy, bulk polymerization of DCPD occurs as a function of catalyst content, 11,12 yet the increased catalyst concentration of Experiment 14 did not yield any toughness recovery.…”
Section: Resultsmentioning
confidence: 99%
“…And finally, the healing agent must have rapid catalyst dissolution (or for liquid catalysts, rapid mixing) and polymerisation kinetics, low shrinkage upon polymerisation, and the resulting polymer should have good mechanical and adhesive properties. Preliminary systems used styrene/polystyrene blends 18 and phenolic based resins 19 in their microcapsules with varying results, but the healing chemistry found to most completely fulfil this daunting set of healing agent requirements is the ring opening metathesis polymerisation (ROMP) [20][21][22] of dicyclopentadiene (DCPD) with the popular ruthenium based olefin metathesis catalyst bis(tricyclohexylphosphine) benzylidine ruthenium dichloride, colloquially referred to as 'Grubbs' catalyst'. [23][24][25][26][27] In this reaction, the highly strained olefin of DCPD coordinates to the ruthenium catalyst, followed by a cycloaddition with the ruthenium-carbene to form a metallocyclobutane intermediate, and finally a cycloreversion to open dicyclopentadiene's strained ring and add an ultimate unit to the growing polymer chain (Fig.…”
Section: Microencapsulated Healing Agentsmentioning
confidence: 99%
“…The normalized integration of original DSC dynamic scan thermograms gives the plot of conversion vs. temperature as shown in Figure 3 The isoconversional method is often employed for the analysis of curing kinetics [39]. Isoconversional analysis method assumes that the reaction rate for a given conversion is only a function of temperature and, hence, allows evaluation of the activation energy as a function of conversion:…”
Section: Dsc Measurements and Cure Kinetic Analysismentioning
confidence: 99%
“…In many systems, nanocomposites have been shown to have increased thermal stability and mechanical performance (strength, stiffness and dimensional stability) compared to neat resin [34][35][36][37][38][39][40]. Compared with many other nano-fillers, alumina nanoparticles are low cost and can be functionalized for nanocomposite fabrication [41 ].…”
Section: Nanoparticles For Composite Enhancementmentioning
confidence: 99%